The Impact of User Experience, and Word-of-Mouth, with Customer Satisfaction as a Mediating Factor in the Oxygen WiFi Network - Ilmi Farisi Khumaini; Maria Christiana Iman Kalis; Bintoro Bagus Purmono; Nur Afifah; Harry Setiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of User Experience and Word of Mouth on Customer Satisfaction in the Oxygen.id Home service, one of the internet providers in Indonesia. In today’s digital era, the quality of internet service is measured not only by connection speed and stability but also by the user’s experience when interacting with the service. User Experience encompasses aspects such as ease of use, interface design, responsiveness, and emotional comfort during service usage. A well-designed User Experience can enhance positive perceptions of the service and lead to increased Customer Satisfaction. Customer Satisfaction plays a crucial role as a bridge between User Experience and Word of Mouth. Satisfied customers tend to be more willing to recommend the service to others, either directly or through social media. Word of Mouth serves as a trusted form of organic promotion and has a significant impact on attracting potential new customers. Therefore, Word of Mouth is not only an outcome of good service but also a part of an effective growth strategy in a competitive industry. This study employs a quantitative approach by collecting data through surveys of active Oxygen.id Home users. The analysis results indicate a strong relationship between User Experience, Customer Satisfaction, and Word of Mouth, with Customer Satisfaction acting as a significant mediating variable. These findings emphasize the importance for service providers to continuously optimize User Experience in order to increase customer loyalty and expand market reach through the power of Word of Mouth.